Systematic Review: Scoring Triage in Pandemic Covid-19 - Dinda Sesylia Octaviani; Ridlwan Kamaluddin (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Background: Patients with emergency conditions will get the first health service in the Emergency Room (IGD). The emergency room nurse has an important role in assessing and determining the severity of the patient. The nurse determines the priority of action and the need for treatment in Intensive Care Unit (ICU) using triage. One of the triage that can be done is triage scoring to facilitate nurses in determining high-risk and low-risk patients. Purpose: To find out the triage scoring used during the pandemic. Methods: Literature search is conducted using the PICO framework. This systematic review is limited to articles published from 2019-2021 with articles in English. The database used is Google Scholar. PubMed, Science Direct, and ProQuest which using the keywords score, triage, pandemic and emergency care. Results: Based on the three articles reviewed, an overview of the use of triage scores during a pandemic is obtained using the SODA score, modified PRIEST and double triage and telemedicine protocols. Giving the triage score can make it easier for health workers to identify high-risk patients and prevent unexpected events. Conclusion: Triage scoring can be applied at Covid-19 referral hospitals which helps nurses determine priorities and prevents special mortality in Indonesia, which is experiencing the second wave Keywords: Score, Triage, Pandemic